2023
DOI: 10.3390/rs15092468
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Dust-Storm Transport Pathways Using a Convolutional Neural Network and Geographic Context for Impact Adaptation and Mitigation in Urban Areas

Mahdis Yarmohamadi,
Ali Asghar Alesheikh,
Mohammad Sharif
et al.

Abstract: Dust storms are natural disasters that have a serious impact on various aspects of human life and physical infrastructure, particularly in urban areas causing health risks, reducing visibility, impairing the transportation sector, and interfering with communication systems. The ability to predict the movement patterns of dust storms is crucial for effective disaster prevention and management. By understanding how these phenomena travel, it is possible to identify the areas that are most at risk and take approp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Huang used a physical modeling and numerical simulation to establish a physics-based near-surface wind field statistical model [12]. Yarmohamadi predicted the trajectory of dust storm transport based on convolutional neural networks and geographical environment [13]. Rodakoviski found that current climate models underestimate the time of particle transportation in the air and further investigated it using turbulent motion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Huang used a physical modeling and numerical simulation to establish a physics-based near-surface wind field statistical model [12]. Yarmohamadi predicted the trajectory of dust storm transport based on convolutional neural networks and geographical environment [13]. Rodakoviski found that current climate models underestimate the time of particle transportation in the air and further investigated it using turbulent motion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al, 2015) used physical modeling, numerical simulation and other methods to build a physics-based statistical model of the near-surface wind field. (Yarmohamadi et al, 2023) predicted the transport path of dust storms based on convolutional neural networks and geographical environment. (Rodakoviski et al, 2023) found that current climate models underestimate how long particles travel through the air, and used eddy motion to further understand it.…”
Section: Introductionmentioning
confidence: 99%